Hierarchy and Its Discontents : Culture and the Politics of Consciousness in Caste Society - Parish, Steven M. (University of Pennsylvania Press, 2016)
The caste system fascinates Western scholars because it forms the basis for South Asian society--but how does it affect its participants?